Pandangan Ideologis Paham Keagamaan Hizbut Tahrir Indonesia (HTI) dalam Sistem Kenegaraan di Indonesia - Alwanda Putra; Rudy Erdianto; Farhan Hidayat (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Hizbut Tahrir Indonesia (HTI) is a trans-national Islamic movement and carrying the re-establishment of a global Islamic caliphate. Theoretically, this establishment addressed for the sake of Islamic law at the level of politics and society. The problem is, when the ideas and struggles were developed in Indonesia, which has the basic form of the state and the fnal state, namely the Republic of Indonesia (NKRI) and the Pancasila, the struggle HTI is part of the defamation against the state. Although this political struggle will not succeed, but it is quite efective conduct of delegitimation on national awareness among Muslims that they managed to recruit a member. This article will explain the state of political ideology and agenda HTI. Therefore, this paper aims to explore the views HTI about sharia and its position for the state system of caliphate and the glory (political) Islam that sought to establish global world as well as in Indonesia nationally. In addition, HTI put ideological struggle in the context of the ideological threat on Pancasila and the Homeland, because the idea khilafahnya necessarily contradictory with the nation-state of the Republic of Indonesia. The data of this article comes from the literature. The results of the literature review were then analyzed through political discourse and the Islamic state, which raises the style Islamic political discourse in the context of political discourse HTI in Indonesia. The article concludes, HTI do delegitimation nationality, Pancasila and state buildings Homeland. It departs from the perspective of Islamic law formalist and holistic, where Sharia law is understood as the rules governing the whole life of the community, through the formalization into the constitution and state law. Cita re-establishment of the Islamic caliphate is a structural condition for the enforcement of Islamic Shari’a.